The Evolution and Diversity of Interleukin-17 Highlight an Expansion in Marine Invertebrates and Its Conserved Role in Mucosal Immunity - Saco, Amaro; Rey-Campos, Magalí; Rosani, Umberto; Novoa, Beatriz; Figueras, Antonio (Frontiers in Immunology, 2021)
The interleukin-17 (IL-17) family consists of proinflammatory cytokines conserved during evolution. A comparative genomics approach was applied to examine IL-17 throughout evolution from poriferans to higher vertebrates. Cnidaria was highlighted as a putative ancestral phylum, and several evolutionary patterns were revealed. Large expansions of the IL-17 repertoire were observed in marine molluscs and echinoderm species. We further studied this expansion in filter-fed Mytilus galloprovincialis, which is a bivalve with a highly effective innate immune system supported by a variable pangenome. We recovered 379 unique IL-17 sequences and 96 receptors from individual genomes that were classified into 23 and 6 isoforms after phylogenetic analyses. Mussel IL-17 isoforms were conserved among individuals and shared between closely related Mytilidae species. Certain isoforms were specifically implicated in the response to bath infection in mussel gills. The involvement of IL-17 in mucosal immune responses could be conserved in higher vertebrates from these ancestral lineages.